Pelatihan Pencatatan Dan Penyusunan Laporan Keuangan Bagi Siswa SMK Swasta Setia Budi Abadi Perbaungan - Muhammad Harpis; Nova Lega Hati Siregar; Retno Nela Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service activity aims to provide an understanding of the basics of preparing financial reports for students of SMK Swasta Setia Budi Abadi Perbaungan. An understanding of the preparation of financial statements, although in a simple way, is needed for Vocational High School (SMK) students, to apply the theory gained in college. The method used in this community service activity is in the form of training from lecturers to students of SMK Swasta Setia Budi Abadi Perbaungan. From this training activity, it can be seen that the students of SMK Al-Falah understand the material presented by the lecturer, as can be seen from the enthusiasm of the students in the questions asked. This activity is expected so that students can understand how to record and prepare reports, so that when they enter the community, they are able to adapt well.